City Movers - Okwuonu, Chinwe (Literamed Publications Nigeria Ltd, 2005)
City Movers is a story of love,intrigue,hatred,fame,deceit, and treachery.It is the story of Oluike, who in search of fame and wealth, becomes a politician;of laura, who in search of true love became a prostitute;of Greg, who in search of good means of livelihood,becomes a notorious thug;and of passionate men and women who do everything within their means to shake the city they live in.
Keywords: Fiction; Juvenile Literature